Parasitism in eggs of Paraselenis flava (Coleoptera: Chrysomelidae) in sweet potato (Ipomoea batatas) - MONTES, SÔNIA MARIA N. M.; COSTA, VALMIR A. (Revista Colombiana de Entomología, 2011)
The occurrence of Emersonella pubipennis (Hymenoptera: Eulophidae) parasitizing eggs of Paraselenis flava (Coleoptera: Chrysomelidae) infesting sweet potato, (Ipomoea batatas), in the region of Presidente Prudente, state of São Paulo, Brazil, is reported.